Досвід та висновки організації діяльності міліції Української РСР у 1948 році - Бандурка, О. М.; Bandurka, O. M.; ORCID: http://orcid.org/0000-0002-0240-5517; Греченко, В. А.; Grechenko, V. A.; ORCID: http://orcid.org/0000-0002-6046-0178 (Європейські перспективи. - 2021. - № 3. – С. 5-14, 2021)
Визначено, що діяльність міліції у 1948 р. мала свої особливості, пов’язані з політичною та соціально-економічною ситуаціями в державі. Новизна статті в тому, що у ній вперше вивчено основні напрями роботи міліції у конкретний історичний період - 1948р., доповнено питання про структурні зміни в організації міліції УРСР, характеристика Дисциплінарного статуту міліції, протидія міліції різним видам злочинності, зокрема економічній злочинності, в науковий обіг уведено значною мірою новий фактичний матеріал про стан злочинності, успіхи та недоліки у її подоланні.

The activities of the militia in 1948 had their own peculiarities related to the political and socioeconomic situation in the country. The post-war devastation in Ukraine had not yet been finally overcome, its population was struggling to recover from the famine of 1946-1947, and the card system had just been abolished and monetary reform carried out. The criminogenic situation in the republic was significantly influenced by the moral and psychological situation in society - the habit of violence and the use of weapons that appeared during the war, as well as the presence of a large number of them on hand, which was also a consequence of the war. The abolition of the death penalty in May 1947 had a negative effect on the fight against crime. A review of the literature shows that this scientific problem is insufficiently studied. The novelty of the article is that it first studied the main directions of militia work in this particular historical period - 1948, supplemented the issue of structural changes in the organization of the militia of the USSR, the characteristics of the Disciplinary Statute of the militia. A large amount of new factual material on the state of crime, successes and shortcomings in overcoming it has been introduced.

Установлено, что деятельность милиции в 1948 г. имела свои особенности, связанные с политической и социально-экономической ситуациями в государстве. Новизна статьи в том, что в ней впервые изучены основные направления работы милиции в конкретный исторический период - 1948г., дополнен вопрос о структурных изменениях в организации милиции УССР, характеристика Дисциплинарного устава милиции, противодействие милиции разным видам преступности, в частности, экономической преступности, в научное обращение введен в значительной степени новый фактический материал о состоянии преступности, успехах и недостатках в ее преодолении.
Бандурка, О. М. Досвід та висновки організації діяльності міліції Української РСР у 1948 році / Бандурка Олександр Маркович, Греченко Володимир Анатолійович // Європейські перспективи. - 2021. - № 3. – С. 5-14. - DOI: 10.32782/EP.2021.3.1.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Україна. Ukraine. Украина; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal affairs agencies; органы внутренних дел; міліція; militia; милиция; Дисциплінарний статут міліції; Police Disciplinary Statute; Дисциплинарный устав милиции; протидія злочинності; crime prevention; противодействие преступности